2010
DOI: 10.1021/ja909371t
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of C−F Reductive Elimination from Palladium(IV) Fluorides

Abstract: The first systematic mechanism study of C–F reductive elimination from a transition metal complex is described. C–F bond formation from three different Pd(IV) fluoride complexes was mechanistically evaluated. The experimental data suggest that reductive elimination occurs from cationic Pd(IV) fluoride complexes via a dissociative mechanism. The ancillary pyridyl-sulfonamide ligand plays a crucial role for C–F reductive elimination, likely due to a κ3 coordination mode, in which an oxygen atom of the sulfonyl g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
167
1
12

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 279 publications
(184 citation statements)
references
References 128 publications
4
167
1
12
Order By: Relevance
“…Much of this recent activity is driven by the need for synthetic procedures to incorporate fluorine or a CF 3 group strategically in the synthesis of pharmaceuticals or PET reagents, leading to the development of new methodology for formation of C-F and C-CF 3 bonds [110][111][112][113][114][115][116][117][118][119][120][121][122]. Organometallic chemistry involving the chemical functionalization of C-F bonds also continues to be an active field [123][124][125][126][127][128][129][130][131][132][133][134][135][136].…”
Section: [ ( S C H E M E _ 4 ) T D $ F I G ]mentioning
confidence: 99%
“…Much of this recent activity is driven by the need for synthetic procedures to incorporate fluorine or a CF 3 group strategically in the synthesis of pharmaceuticals or PET reagents, leading to the development of new methodology for formation of C-F and C-CF 3 bonds [110][111][112][113][114][115][116][117][118][119][120][121][122]. Organometallic chemistry involving the chemical functionalization of C-F bonds also continues to be an active field [123][124][125][126][127][128][129][130][131][132][133][134][135][136].…”
Section: [ ( S C H E M E _ 4 ) T D $ F I G ]mentioning
confidence: 99%
“…[16] A fundamental understanding of the nature of transition-metal fluorides and the ability to predict their reactivity are still lacking: For example, fluoride ligands bound to sulfonamide-supported Pd II or Pd IV complexes persist in wet organic solvents, whereas the fluoride ligand on Pd II BrettPhos complexes shows pronounced basic properties, with likely hydrolysis of the metal-fluorine bond. [3,4] Given our poor fundamental understanding of the properties of metal fluorides, tailoring the properties of the metal fluoride to the desired transformation is hardly possible, and further research is warranted to gain insight into the promising area of metal-bound fluoride chemistry.…”
mentioning
confidence: 99%
“…Among Toste's wide substrate survey, several of the alkyl fragments underwent rearrangements characteristic of carbocations. For example, a methyl [1,2]-rearrangement was dominant in the fluorination of a gold(I) neopentyl complex. Reaction of alkylgold(III) difluoride was found to have a kinetic inverse order in added fluoride, which supports the authors' proposed mechanism of fluoride dissociation followed by concerted C-F reductive elimination from tricoordinate cationic gold(III).…”
Section: Reactions Proposed To Proceed Via Two-electron Pathwaysmentioning
confidence: 99%
“…The fundamental organometallic transformation of C-F reductive elimination from a transition metal center was only established in 2008 [1,2], despite years of concentrated effort [3]; however, in the following decade, the rapid growth of organotransition metal fluorine chemistry has enabled the synthesis of fluorinated organic molecules that were previously challenging to access [4][5][6][7]. Further work has shown that synthetically useful C-F bond forming reactions can be achieved through diverse organometallic mechanisms, including C-F reductive elimination, electrophilic metal-F bond cleavage, and a variety of single-electron pathways.…”
Section: Introductionmentioning
confidence: 99%